PECULIARITIES OF INNERVATION OF MUSCLES AND SKIN OF THE ANTERIOR AND LATERAL ABDOMINAL WALLS IN HUMAN FETUSES - Khmara, T.V.; Stelmakh, G.Ya.; Garvasiuk, O.V.; Biriuk, I.G.; Drachuk, V.M. (World of Medicine and Biology, 2022)
Considering theoretical and practical importance of data regarding fetal anatomical variability of intercostal nerves, iliopsoas and inguinal nerves, the study was performed on 44 preparations of human fetuses of 231.0–375.0 mm parietococcygeal length using macromicroscopic preparation, superficial staining of dissected nerves, and morphometry. In some cases, in the innervation of the muscles and skin of the anterior and lateral abdominal walls took part VI (V)–XII intercostal nerves and iliohypogastric nerve, and in other – VII–XII intercostal nerves, iliohypogastric and ilioinguinal nerves. The formation of the intramuscular nerve plexus of the abdomen involves branches that begin directly from the main trunks of the intercostal nerves, and also from the lateral, anterior and additional musculocutaneous branches of the intercostal nerves, and the branches of the iliohypogastric and ilioinguinal nerves. In human fetuses, there are areas of overlap between the innervations of the muscles and skin of the anterior and lateral abdominal walls.